The Prevalence of Post-Traumatic Stress Disorder on Healthcare Workers During the Covid-19 Pandemic: Literature Review (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
Preventing symptoms of post-traumatic stress disorder (PTSD) that health workers face during the current COVID-19 pandemic is a worldwide challenge, as healthcare workers may experience chronic, often unpredictable work stressors that lead to PTSD. This review aimed to describe the prevalence of post-traumatic stress disorder worldwide. As part of this review, we searched MEDLINE, PubMed, Google Scholar, and Crossref for publications using selected keywords. The Articles have been reviewed and classified into one or more categories based on Topics: prevalence of post-traumatic stress disorder (PTSD). A total of 13 publications fit our inclusion criteria. Here The findings of the review show the prevalence is high in Spain, Italy, and the USA; the mean shown in the review is 13,3% of PTSD. Highlight the need for urgent interventions to protect healthcare workers from the psychological impact of pandemic-related traumatic events leading to PTSD. Health care Policies must consider strategies for preventing and managing PTSD and related mental disorders.